2005
DOI: 10.1111/j.1600-0897.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Inhibitory‐Motif Killer Immunoglobulin‐Like Receptor, KIR2DL1, is Increased in Natural Killer Cells from Women with Pelvic Endometriosis

Abstract: ITIM-KIR expressing NK cells might confer tolerance to peritoneal endometriotic implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 18 publications
1
58
0
3
Order By: Relevance
“…These facts, such as it has been recently proposed for endometriosis, suggest that CD56 NK cells Table 4. HLA-C alleles and phenotypes in melanoma patients and controls positive for KIR2DL1/S1 might contribute to the induction of tolerance against melanoma (45). Moreover, these findings might support the observation of Guillot et al (46), about the absence of a link between the effect of IFN-a on perforin expression in cytotoxic cells and the posttherapeutic disease evolution, because the expression of KIR receptors on cytotoxic NK cell surface could, at least partially, block the antitumoral function of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…These facts, such as it has been recently proposed for endometriosis, suggest that CD56 NK cells Table 4. HLA-C alleles and phenotypes in melanoma patients and controls positive for KIR2DL1/S1 might contribute to the induction of tolerance against melanoma (45). Moreover, these findings might support the observation of Guillot et al (46), about the absence of a link between the effect of IFN-a on perforin expression in cytotoxic cells and the posttherapeutic disease evolution, because the expression of KIR receptors on cytotoxic NK cell surface could, at least partially, block the antitumoral function of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the number of peripheral blood and abdominal NK cells in EMS patients has no significant difference ( Oosterlynck et al 1994, Matsuoka et al 2005. However, the activity visibly weakens, and the impaired degree of NK cell activity positively correlates with EMS development.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that KIRs expressed on NK cells can respond to their HLA class I ligands on eutopic endometrium [39][40][41]. It was also reported that progesterone induces HLA class I mRNA expression by cultured cells from secretory endometrium [51].…”
Section: Hla Class Iamentioning
confidence: 87%
“…In women with endometriosis, expression of inhibitory killer immunoglobulin-like receptors on NK cells from PB and PF is significantly upregulated compared with the level of expression in women without endometriosis [39][40][41], indicating a decrease of NK cell activity and cytotoxicity for endometriotic cells.…”
Section: Nk Cells and Endometriosismentioning
confidence: 93%
See 1 more Smart Citation